Legal insanity and the brain: science, law and European courts : with a foreword by Justice András Sajó, Vice-President of the European Court of Human Rights - Moratti, Sofia; Patterson, Dennis M. (Hart Publishing, 2016)
Introduction / Sofia Moratti and Dennis Patterson -- The neurobiology of antisocial and amoral behaviour : insights from brain science and implications for law / Cole Korpnay and Michael Koenigs -- 'Neuroscepticism' in the courtroom : the limited role of neuroscientific evidence in Belgian criminal proceedings / Katrien Hanoulle and Frank Verbruggen -- France. Is the evidence too cerebral to be cartesian? / Rafael Encinas de Muñagorri and Claire Saas -- 'Not guilty by reason of insanity' in the Italian jurisdiction. A neuroscience revolution? / Barbara Bottalico and Amedeo Santosuosso -- Legal insanity and neurolaw in the Netherlands : developments and debates / Gerben Meynen -- On the abolition and reintrroduction of legal insanity in Sweden / Tova Bennet and Susanna Radovic -- Abolishing the insanity verdict in the United Kingdom : a better balance between legal rules and scientific understanding? / Lisa Claydon and Paul Catley -- Legal insanit in the age of neuroscience / Stephen J Morse